A case of lung abscess successfully treated by transbronchial drainage using a guide sheath. Issue 3 (24th March 2017) - Izumi, Hiroki; Kodani, Masahiro; Matsumoto, Shingo; Kawasaki, Yuji; Igishi, Tadashi; Shimizu, Eiji
Abstract : A 51‐year‐old man was diagnosed with colon cancer in September 2011, and a solitary pulmonary nodule was detected by computed tomography (CT) scan. We performed a transbronchial biopsy with endobronchial ultrasonography using a guide sheath (GS) and diagnosed lung metastasis of colon cancer. The patient experienced remittent fever after the biopsy in spite of intravenous antibiotic therapies. Moreover, his CT scan showed a large lung abscess at the biopsy site. We performed transbronchial drainage using a GS as salvage therapy. The bloody pus was successfully aspirated, and chest X‐ray following the procedure showed dramatic shrinkage of the abscess. Abstract : We report the first successful case of transbronchial drainage using guide sheath (GS) for lung abscess complicated by bronchoscopic biopsy. This treatment procedure using GS may be an effective and safe strategy in the treatment of lung abscess with airway connection in patients who are refractory to antibiotic therapy.